Estudo sobre as tecnologias digitais de informação e comunicação como mediadoras da construção do conhecimento na percepção de professores em formação e de crianças do ensino fundamental - Falcão, Patricia Mirella de Paulo (Universidade Federal de São Carlos, 2015)
Contemporary society poses distinct characteristics in our daily lives. Perhaps one of the most significant is the fast dissemination of information. This fact is made possible by the Digital Technologies of Information and Communication (TDIC). Together with the various inventions of these technologies there is an increasing access by the various social classes of the country. One reason for this growth is the cheapening of such technologies. Thus, they became part of social life and encompassed various sectors such as political and educational, in an irreversible process. Having the educational context in mind, there are discussions about the difficulty in defining the role of the teacher between the learner and the TDIC. Being sometimes mediator and user, the teacher and the school in general, are strongly charged, because, it seems, there is a gap in the education sector related to the use and integration of such technologies in the teaching-learning process. Another view is related to students. These are constantly and heavily exposed to such technologies, having constant usage and demonstrating apparent mastery of TDIC. Therefore, issues involving teachers, during their graduation and digital technologies have been widely discussed. This research aimed to study teachers during their graduation and children between 9 and 11 years old, relating their knowledge and practices through the use of TDIC, and whether there is a gap between these subjects, considering such knowledge. In order to make the analysis possible, there are four specific objectives: Identify the profile of children between 9 and 11 years, relating their knowledge, use and practice with the TDIC; To characterize the profile of pedagogy students from the middle period of the course regarding their knowledge on TDIC; Check the distance or proximity between teaching and training children, related to the degree of knowledge and use of TCID; Suggest new digital teaching model training and literacy for teachers who work or will work with the resources of TDIC in their disciplines. In view of the objective of the research a methodological triangulation through interviews and questionnaires was held, conducting qualitative and quantitative analysis for the proposed study. The analysis showed that there is a strong technological speech in the process of mediation between children and TDIC, maybe not so faithful to the reality of knowledge by the children. The complete investigation process brought to light a number of issues and possibilities for future research, but one of the most important conclusions is that the teacher training is facing at least two challenges: the first related to the knowledge they are getting at the university on such theme and the second is on its mediating role in knowledge production, using the resources of TDIC this process.
Study on the digital information and communication technologies as mediators of the knowledge construction in the perception of teachers during their graduation and children from the basic education
Keywords: Tecnologia educacional; Professores - formação; Tecnologias digitais; Educação; Informática; Criatividade nas crianças; Teacher graduation; Digital Technology of information and communication; Child creativity; Education; Information science; OUTROS